Be a teacher of Rural Schools in Paraná/BR between 1915 and 1946 - Denize Santi; André Paulo Castanha (Universidade Federal do Norte do Tocantins, 2023)
This article analyzes the relationship between the organization of the rural school and the teachers in the State of Paraná between 1915 and 1946. The time frame is linked to the educational legislation, being the year 1915, marked by a law of the state of Paraná that brought for the first the name rural school. As a final cut, we define 1946, the year of the implementation of the Organic Law of Primary Education and the Organic Law of Normal Education. The investigation included reports, laws, and decrees, among others, in addition to making use of bibliographies on the subject. When it comes to teachers and their relationship with rural education, the speeches of the time highlighted the importance of the teacher in rural schools, as they assumed all responsibilities for the execution of teaching, being considered the pivot of instruction. However, despite indicating the importance of the teacher, the reports attribute to them the responsibility for the difficulties faced by education, associating, especially, the lack of teacher training, since teachers without training worked, especially in rural schools. In view of this, the State sought alternatives to train teachers, with the installation of rural complementary schools, despite this; we showed that there were few trained teachers who worked in rural education in the period.